2014
DOI: 10.3762/bjoc.10.171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of isoprenoid bisphosphonate ethers through C–P bond formations: Potential inhibitors of geranylgeranyl diphosphate synthase

Abstract: SummaryA set of bisphosphonate ethers has been prepared through sequential phosphonylation and alkylation of monophosphonate ethers. After formation of the corresponding phosphonic acid salts, these compounds were tested for their ability to inhibit the enzyme geranylgeranyl diphosphate synthase (GGDPS). Five of the new compounds show IC50 values of less than 1 μM against GGDPS with little to no activity against the related enzyme farnesyl diphosphate synthase (FDPS). The most active compound displayed an IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Not only has our work demonstrated potential for GGDPS inhibitors as antimyeloma agents (Holstein and Hohl, 2011;Zhou et al, 2014a;Dykstra et al, 2015), but there has also been interest in the use of GGDPS inhibitors as anticancer agents for solid tumors models (Reilly et al, 2016) and in nonmalignant conditions such as pulmonary fibrosis (Osborn-Heaford et al, 2015). Previous efforts to develop GGDPS inhibitors have focused in large part on branched compounds, including V-shaped inhibitors such as DGBP and its analogs as well as more recently U-shaped inhibitors (Wiemer et al, 2007;K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). Prior crystallography studies demonstrated that the V-shaped compounds can occupy both the FDP and the GGDP sites (K- M Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only has our work demonstrated potential for GGDPS inhibitors as antimyeloma agents (Holstein and Hohl, 2011;Zhou et al, 2014a;Dykstra et al, 2015), but there has also been interest in the use of GGDPS inhibitors as anticancer agents for solid tumors models (Reilly et al, 2016) and in nonmalignant conditions such as pulmonary fibrosis (Osborn-Heaford et al, 2015). Previous efforts to develop GGDPS inhibitors have focused in large part on branched compounds, including V-shaped inhibitors such as DGBP and its analogs as well as more recently U-shaped inhibitors (Wiemer et al, 2007;K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). Prior crystallography studies demonstrated that the V-shaped compounds can occupy both the FDP and the GGDP sites (K- M Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallography studies revealed that the V-shaped compound occupied the FDP substrate binding site as well as the GGDP product site within the enzyme's active site (K-M Chen et al, 2008). Subsequent efforts focused on modifications of the V-shaped motif (K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). More recently, a series of triazole bisphosphonates were prepared and it was determined that a mixture of geranyl and neryl triazole bisphosphonates (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our laboratory has generated a novel library of six bisphosphonate compounds capable of inhibiting GGDPS at concentrations below 1 μM while having little to no activity against FDPS [23]. Based on the data from studies with the isolated GGDPS enzyme (Figure 2),[23] we expected the greatest biological activity in vitro to be found with compound 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab reported the synthesis of a library of six new bisphosphonates, basing their structural design on the parental compound DGBP (Figure 2, 3 ) with the alterations of an additional oxygen on the geminal carbon and varied isoprenoid chain lengths (Figure 2 compounds 4 – 9 ) [23]. The additional oxygen substituent was intended to lower each compound’s pK a3 ,[24] and consequently increase biological activity, while the varying isoprenoid lengths were prepared to identify the better structure(s) for potently targeting GGDPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation